A Chemical Biology Approach to Probing the Folding Pathways of the Inhibitory Cystine Knot (ICK) Peptide ProTx-II - McCarthy, Stephen; Robinson, Jenna; Thalassinos, Konstantinos; Tabor, Alethea B. (Frontiers in Chemistry, 2020)
Peptide toxins that adopt the inhibitory cystine knot (ICK) scaffold have very stable three-dimensional structures as a result of the conformational constraints imposed by the configuration of the three disulfide bonds that are the hallmark of this fold. Understanding the oxidative folding pathways of these complex peptides, many of which are important therapeutic leads, is important in order to devise reliable synthetic routes to correctly folded, biologically active peptides. Previous research on the ICK peptide ProTx-II has shown that in the absence of an equilibrating redox buffer, misfolded intermediates form that prevent the formation of the native disulfide bond configuration. In this paper, we used tandem mass spectrometry to examine these misfolded peptides, and identified two non-native singly bridged peptides, one with a Cys(III)-Cys(IV) linkage and one with a Cys(V)-Cys(VI) linkage. Based on these results, we propose that the C-terminus of ProTx-II has an important role in initiating the folding of this peptide. To test this hypothesis, we have also studied the folding pathways of analogues of ProTx-II containing the disulfide-bond directing group penicillamine (Pen) under the same conditions. We find that placing Pen residues at the C-terminus of the ProTx-II analogues directs the folding pathway away from the singly bridged misfolded intermediates that represent a kinetic trap for the native sequence, and allows a fully oxidized final product to be formed with three disulfide bridges. However, multiple two-disulfide peptides were also produced, indicating that further study is required to fully control the folding pathways of this modified scaffold.